The Potential of Educational Transactional Analysis for Human Rights Education - Piotr Toczyski (Edukacyjna Analiza Transakcyjna)
Human Rights Education (HRE) is a dynamic initiative fostering knowledge, values, and skills for the promotion and protection of human rights. Rooted in principles like dignity and justice, HRE empowers individuals to actively contribute to human rights advancement. The European Union Agency for Fundamental Rights (FRA) exemplifies this commitment, engaging in initiatives to raise awareness and understanding of human rights principles. Concurrently, Educational Transactional Analysis  applies TA theory to educational settings, enhancing communication and relationships. TA, with its Parent, Adult, and Child Ego States, aligns with HRE principles, promoting self-awareness and empathy. Applying TA in HRE involves recognizing emotional responses and understanding social and historical contexts. Integrating TA concepts enriches the educational experience, fostering an empathetic and communicative environment. The study applies TA concepts to real-life dialogues, exploring their applicability in HRE. Results reveal TA's potential to address workplace and educational challenges, aligning with HRE principles of open communication, conflict resolution, and rights-respecting dialogue. The intersection of TA and HRE provides a comprehensive framework for enhancing social interactions and promoting human rights principles.